Health and behaviour problems at 8 weeks as predictors of behaviour problems at 8 months. Issue 2 (1st August 1999) - Spencer, N J; Coe, C
Abstract : OBJECTIVE: To assess the value of health and behavioural problems at 8 weeks as predictors of behavioural problems at 8 months in a whole year birth cohort. STUDY DESIGN: Prospective birth cohort study. SETTING: The socially and ethnically diverse city of Coventry. MAIN OUTCOME: Parent reported behavioural problems at 8 months. METHOD: Parent reported infant health and behaviour data were collected, using a validated questionnaire administered by the family health visitor at 8 weeks and 8 months, on 1541 infants participating in the Coventry cohort study. Sociodemographic data were collected at the health visitor's initial visit. Unadjusted relative risks (with 95% confidence intervals (CI)) of behaviour problems at 8 months by sociodemographic variables and health and behavioural problems at 8 weeks were estimated. Adjustment for confounding was made by logistic regression. RESULTS: Infants reported to have behavioural problems at 8 weeks had a significant risk of parent reported behavioural problems at 8 months (adjusted relative risk, 3.44; 95% CI, 1.95 to 6.09) after adjustment for other health outcomes and sociodemographic factors. Of infants with behavioural problems by 8 weeks of age, 19.1% were reported to have behavioural problems at 8 months. CONCLUSIONS: Infants whose parents report behaviour problems by 8 weeks of age are at higher risk of behavioural problems at 8 months. However, despite the higher risk, the proportions of infants identified by behaviour at 8 weeks were too small for the early outcomes to be useful as predictors of behaviour at 8 months in the whole infant population.